A Control Technique of Stepper Motors for Simulated Altitude Indicator Development Used in Helicopter Simulator - Rijanto, Estiko (Pusat Penelitian Informatika - LIPI, 2010)
A helicopter simulator has to be built to fully resemble the real cockpit environment including its instruments. A simulated instrument incorporates mechatronics technology where a mechanical system is electronically controlled to indicate a certain flight variable. This paper describes development of a simulated altitude indicator (SAI) used for a super puma helicopter simulator. This indicator has a main pointer which can rotate 100 times, a small pointer which can rotate 10 times, and a triangular pointer which can rotate once. The novel feature of this paper is that the main and small pointers are actuated by ready on the self stepper motors, instead of commonly used synchros. A control technique is proposed to rotate the motor, and the positioning error is minimized by software compensator. From the repetitive precision experimental result it was obtained that the developed SAI could work well with the degree of precision of 0.03 (dial memory) for the main pointer and 0.22 (dial memory) for the small pointer.